2011
DOI: 10.1186/1472-6947-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of internet access and utilization by medical students in Lahore, Pakistan

Abstract: BackgroundThe internet is increasingly being used worldwide in imparting medical education and improving its delivery. It has become an important tool for healthcare professionals training but the data on its use by medical students in developing countries is lacking with no study on the subject from Pakistan. This study was, therefore, carried out with an aim to evaluate the pattern of internet access and utilization by medical students in Pakistan.MethodsA structured pre-tested questionnaire was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 22 publications
(28 reference statements)
2
35
0
1
Order By: Relevance
“…In a study which was conducted in Meerut, India, Maroof KA and co-workers [10] showed that the main use of the Internet was for communication (58.5%) and entertainment (46.3%) and that only about one-fifths of the respondents used the Internet for searching literature for projects from the medical journals which are there on the Internet. Jadoon et al, [11] stated that 61.0% used the internet for both academic and Personal activities, while 17% used it for academic activities [Table /Fig-3]. …”
Section: Resultsmentioning
confidence: 99%
“…In a study which was conducted in Meerut, India, Maroof KA and co-workers [10] showed that the main use of the Internet was for communication (58.5%) and entertainment (46.3%) and that only about one-fifths of the respondents used the Internet for searching literature for projects from the medical journals which are there on the Internet. Jadoon et al, [11] stated that 61.0% used the internet for both academic and Personal activities, while 17% used it for academic activities [Table /Fig-3]. …”
Section: Resultsmentioning
confidence: 99%
“…Technology plays a crucial role in improving the education and practice of health workers in developing countries (Pakenham-Walsh et al 1997). In these contexts, ICTs can enable students and professionals to access up-to-date information and learning materials (Katikireddi 2004;Jadoon et al 2011), and these individuals may, in turn, reach a much larger group of 'final beneficiaries' (Chandrasekhar & Ghosh 2001). Currently, the evidence appears to suggest potential rather than achievement.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of this, there is need for the providers to brace up and adopt ICT in their practice in order to enhance the emerging consumer-driven health information system such that will improve care process and outcome. Various studies [4,[20][21][22] reported that ICT use has become advanced among healthcare providers, it has become one source of information for care process and there is observed high and widespread usage of computer and the Internet. However, other studies [23-25 and 16] reported hindered access to the Internet, underutilization of evidence-based sources such as computer and the Internet in the delivery of healthcare services and obvious IT-skill gaps among healthcare providers.…”
Section: Introductionmentioning
confidence: 99%